PENINGKATAN PENGETAHUAN GURU OLAHRAGA DAN SISWA SEKOLAH DASAR TENTANG PENCEGAHAN SERTA PENANGANAN AWAL CEDERA OLAHRAGA DI KOTA BANJARMASIN - Uswatun Hasanah; Akhmad Ridhani; Utomo Wicaksono; Rizky Ridhayanti; Bernadus Sadu; Juliani Saputri; Dadan Prayogo (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Sports injuries are a problem that often occurs in school-age children and can affect students' learning and physical activities. Lack of knowledge about the prevention and early treatment of sports injuries in physical education teachers and students can increase the risk of mishandling injuries in the school environment. This community service activity aims to improve the knowledge and skills of elementary school sports teachers throughout the city of Banjarmasin and students of SDIT Ukhuwah Banjarmasin regarding the prevention and early handling of sports injuries. The methods used are in the form of a participatory educational approach through lectures, demonstrations of PRICE techniques (protection, rest, ice, compression, elevation), re-demonstrations, and question and answer sessions. The activity was carried out face-to-face by involving sports teachers and elementary school students as participants. The results of the activity showed an increase in participants' understanding of the types of sports injuries, injury prevention efforts, and appropriate early handling of sports injuries. In addition, participants were able to re-practice the PRICE technique independently well during the re-demonstration session. This activity shows that practice-based education is effective in improving sports health literacy and injury preparedness in the school environment.